Effect of conductive additives on the transport properties of porous flow-through electrodes with insulative particles and their optimization for Faradaic deionization. (15th November 2019) - Reale, Erik R.; Shrivastava, Aniruddh; Smith, Kyle C.
Abstract: Deionization devices that use intercalation reactions to reversibly store and release cations from solution show promise for energy-efficient desalination of alternative water resources. Intercalation materials often display low electronic conductivity that results in increased energy consumption during desalination. Accordingly, we performed experiments to quantify the impact of the size and mass fraction of conductive additives and insulative active particles on the effective electronic conductivity, ionic conductivity, and hydraulic permeability of porous electrodes. We find that Ketjen black conductive additives with nodules <50 nm in diameter produce superior electronic conductivity at lower mass fractions than the larger carbon blacks commonly used in capacitive deionization. Hydraulic permeability and effective ionic conductivity depend weakly on carbon black content and size, though smaller active particles decrease hydraulic permeability. Based on these results we analyzed the energy consumption and salt removal rate of different electrode formulations by constructing an electrochemical Ashby plot predicting the variation of desalination performance with electrode transport properties. Optimized electrodes containing insulative Prussian blue analogue (PBA) particles were then fabricated and used in an experimental cation intercalation desalination (CID) cell with symmetric electrodes. For 100 mM NaCl influent energy consumption varied from 7 to 33 kJ/mol when current density increased from 1 to 8 mA/cm 2, approaching ten-fold increased salt removal rate at similar energy consumption levels to past CID demonstrations. Complementary numerical and analytical modeling indicates that further improvements in energy consumption and salt removal rate are attainable by enhancing transport in solution and within PBA agglomerates. Graphical abstract: Image 1 Highlights: Transport properties of desalination electrodes are characterized experimentally. Nanoscopic conductive additives are found to enhance electronic percolation. Material selection criteria are introduced based on desalination energy and rate. Cation intercalation desalination cell demonstration shows ∼10X rate improvement.